Effectiveness Model Learning Interactive on Eye Lesson PKn di Class Low - Ramadhani, Suci (International Journal of Students Education, 2025)
This study aims to evaluate the effectiveness of interactive learning models in Citizenship Education (PKN) subjects in lower grades through a literature review method. Civics learning at the elementary school level requires an innovative approach so that students can understand abstract concepts, such as rights and obligations, more easily and enjoyably. One approach used is the interactive learning model, which prioritizes active student involvement in various activities such as discussions, role plays, and simulations. Through a review of various literature sources, this study found that interactive learning models can increase student engagement, understanding of Civics concepts, and develop students’ social and emotional skills. In addition, this model can also increase student learning motivation, make learning more enjoyable, and enrich the learning experience with the use of technology. However, the implementation of this model also faces several challenges, including limited time, facilities, and teacher skills in managing interactive classes. Based on the results of the review, it can be concluded that the interactive learning model is effective in improving students’ understanding and motivation in Civics learning, with the note that these challenges must be overcome through teacher training and improving school facilities. Further research is needed to explore innovations in the implementation of this model in lower grades.